Danish Key Performance Indicators for Railway Timetables - Schittenhelm, Bernd; Landex, Alex (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
Based on the first common list of Danish railway timetable evaluation criteria this paper presents a series of existing and newly developed key performance indicators (KPI) for railway timetables. Measuring the level of timetable capacity consumption is done by the well-known UIC 406 methodology. By introducing the concept of timetable patterns it becomes possible to measure how systematic a given timetable is. Robustness of the timetable depends much on the complexity of the planned railway traffic. With the application of timetable fix points a new powerful tool becomes available to measure the robustness potential of a timetable. Societal acceptance of an implemented timetable is crucial for its success. It can be measured with satisfaction surveys. These must be conducted by an independent non-departmental organization to ensure objectivity, as it is done by “Passenger Focus” in the United Kingdom. Short travel and transfer times make the railway competitive. The degree of deviation from the shortest possible travel and transfer time gives an overview of the socio-economic attractiveness of a given timetable. The new KPI have proven useful in their first trial. Most of the presented KPI must be calculated manually but have a high potential to be automated and integrated into future timetabling software packages. Few of the KPI demand a high level of knowledge about railway infrastructure characteristics and basic timetable train path structures. This makes a future automation more difficult. The first trial of the recommended timetable KPI has shown further development possibilities by e.g. looking separately at railway stations when applying the UIC 406 methodology and considering timetable pattern differences when calculating how systematic a timetable is.